Distribution of Antibacterial Resistance among Pathogenic Bacterial Isolates from Patient in Al-Shatrah General Hospital - Baidaa M. Kadim (University of Thi-Qar Journal of agricultural research, 2024)
Nowadays antimicrobial resistance is a huge phenomenon worldwide. The current article aims to detect the most antibiotic resistant among different kinds of antibiotics that extensively use in Iraq, to reduce the antibiotic resistance phenomenon, detect the most effective antibiotic can eliminate or kill pathogenic isolates. Two hundred clinical specimens were collected from patients who are hospitalized Al-Shatrah General Hospital. All samples were directly inoculated in enrichment media after had been obtained from urine, blood, ear swabs, sputum, wound swabs and diagnosed depending on the biochemical tests and molecular investigation that were done. The isolated pathogens were examined against 35 kinds of antibiotic including 13 Beta-lactams, 4 Aminoglycosides, 4 Fluoroquinolones, 3 Macrolides, 2 Glycopeptides, 2 Polymyxins, and one for each of Tetracycline, Chloramphenicol, Nitrofurantoin, Linezolid, Tazobactam, and Bacitracin using Kirby disc diffusion method. The results classified isolated bacteria into 60 (40.8%) isolates Gram-positive and 87 (59.2%) were Gram-negative isolates. While 69 (47%) bacterial isolates were isolated from males; 78 (53%) bacterial isolates were isolated from females, the most common isolated pathogens were Staphylococcus sp. 40 (27%), Streptococcus sp. 20 (13.6%), Proteus sp. 24 (16%), Escherichia coli 29 (19.7%); whereas, the least isolated bacteria is Salmonella typhi 2 (1.4%). While, the highest isolates were 41 isolates (36%) within age group (36-45); the least isolates were 19 isolates (12.9%) within age group (56-65). Bacitracin and Oxacillin were resisted by 10 bacterial species in this study. Also, the results found Levofloxacin, Ceftriaxone, Cefotaxime, Ciprofloxacin, Meropenem, Tazobactam, Imipenem are more effective in compare to other antibiotics.